2011
DOI: 10.4314/ajtcam.v8i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Antiretrovirals and the use of traditional, complementary and alternative medicine by HIV patients in KwaZulu-Natal, South Africa: a longitudinal study

Abstract: The aim of this prospective study (20 months) was to assess HIV patients' use of Traditional, Complementary and Alternative Medicine (TCAM) and its effect on ARV adherence at three public hospitals in KwaZulu-Natal, South Africa. Seven hundred and thirty-five (29.8% male and 70.2% female) patients who consecutively attended three HIV clinics completed assessments prior to ARV initiation, 519 after 6 months, 557 after 12 and 499 after 20 months on antiretroviral therapy (ART). Results indicate that following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 23 publications
3
58
1
Order By: Relevance
“…This finding seems to conform to the findings of a longitudinal study in South Africa showing a reduction of alcohol use with the initiation of ART (Peltzer, Friend-du Preez, Ramlagan, Fomundam, Anderson, & Chanetsa, 2011). This might also be an effecet of health education or counselling with uptake of ART.…”
Section: Discussionsupporting
confidence: 89%
“…This finding seems to conform to the findings of a longitudinal study in South Africa showing a reduction of alcohol use with the initiation of ART (Peltzer, Friend-du Preez, Ramlagan, Fomundam, Anderson, & Chanetsa, 2011). This might also be an effecet of health education or counselling with uptake of ART.…”
Section: Discussionsupporting
confidence: 89%
“…This confirms the findings of a South African study that reported a decreased pattern with CAM use after starting to use ARTs. [36] It is also equally important to note that participants viewed no harm in using CAM with conventional ARTs and believed that one should use as many therapies as possible, provided there are benefits of it. This particular aspect was further supported by a review of published literature on CAM use among HIV population, which reported popular adjunct use of CAM with ARTs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Peltzer et al (2011) and Langlois-Klassen et al (2007), Hypoxis hemerocallidea (African potato), Hypericum perforatum (St. John's wort), Sutherlandia frutescens (Sutherlandia) and Allium sativum (garlic) are some of the most commonly used herbs by HIV-positive people in sub-Saharan Africa.…”
Section: Medicinal Herbs Believed To Have Antiviral Properties and Thmentioning
confidence: 99%